MEMAHAMI KARAKTERISTIK PESERTA DIDIK DALAM PROSES PEMBELAJARAN - Siregar, Muthomainnah; Nurlaeli, Acep; Kosim, Abdul; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
This paper tries to elaborate the ability of educators to understand the characteristics of students by optimizing the achievement of the learing process. At the implementation level, the success of the learning process is certainly related to the ability of educators in understanding students’ subjects that have differences, both physical and non-physical dimensions. Even in the learning process, understanding the characteristics of children becomes a barometer of the success of the learning process. This is because educators are the spearhead of the implementation of learning. To understand children, educators need to use all information both information sourced from internal and external children. The information can be related to child background factors such as children’s socio-cultural factors. These factors are important to understand to optimize the pattern of relationships and interactions between educators and students. Inaddition, student characteristics are related to several important elements such as intellectual aspects, physical, emotional and moral aspects. All these aspects are important to note that the difference in age will determine the difference in treatment. Differences in treatment are increasingly demanded along with changes and developments in technological science.